Carex maolanensis (Cyperaceae), a new species from Guizhou, China - Zhang, Xixi; Yao, Zhengming; Meng, Huili; Deng, Yunfei (Phytotaxa, 2021)
Carex maolanensis, a new species of Cyperaceae is described and illustrated from Guizhou, China. The new species belongs to sect. Decorae, and it is similar to C. jizhuangensis, but differs in having short rhizome, 3–7 spikes per node, terminal spikes androgynous, female glumes awned. The morphology of perigynium and achene of C. maolanensis and C. jizhuangensis is compared. According to the IUCN Red List criteria, it may be turned out to Endangered (EN) or Vulnerable (VU), however, for the present, it is better to be classified as Data Deficient (DD) because the field survey for the species is necessary. A revised identification key to the species of sect. Decorae from China is provided.